Jar burial of Metsamor. Results of the preliminary examination - Piliposyan , Ashot; Simonyan , Hasmik; Jakubiak , Krzysztof; Iskra , Mateush; Zakyan , Tigran; Aleksanyan , Lusine (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
In 2022 Armenian-Polish joint archaeological team conducting scientific research project at the Metsamor archaeological site unearthed one jar/karas burial in the urban quarters. The excavations in the urban quarters of Metsamor started in 2013. The research paper tries to bring up data to more fully understand the ritual practice of jar burials at the site. This paper reviews previous research undertaken at the site and describes the recent excavation which revealed evidence of jar burial practice in the Metsamor archaeological site dating to the 2-3rd centuries AD. The research confirms the use of the urban quarters as a burial area where some structures were used to create a burial space for some individuals (males, females, and children).